Voluntary Disclosure Programs, Tax Morale, and Tax Penalties: Their Influence on Individual Taxpayer Compliance in the Context Tax Regulations Harmonization Law - Arifiana, Zahra; Wahyudi, Slamet (SENTRALISASI, 2025)
This study aims to ascertain how individual taxpayer compliance is affected by tax morality, tax penalties, and voluntary disclosure programs.  At the Kantor Pelayanan Pajak (KPP) Pratama Jakarta Kebayoran Baru Dua, the study was conducted using primary data from surveys.  Later, the data was examined using multiple linear regression analysis.  The study's conclusions imply that tax fines, tax ethics, and voluntary disclosure initiatives have a major influence on individual taxpayer compliance. In theory, this study advances knowledge that voluntary disclosure initiatives may eventually raise taxpayer awareness and compliance.  The internal component of tax morale, which is impacted by societal norms, government trust, and the fairness of the tax system, can be strengthened by the deterrent effect of tax sanctions as an external factor. In practice, this means that while voluntary disclosure programs can boost compliance in the short term, their long-term efficacy hinges on raising taxpayer tax morale through tax education and the imposition of severe but appropriate tax penalties to avoid stifling morale.